2001
DOI: 10.1097/00000539-200106000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hydroxyethyl Starches of Varying Molecular Weights on Platelet Function

Abstract: We evaluated the effect of various hydroxyethyl starch (HES) solutions on platelet function. Blood was obtained before and after the IV infusion (10 mL/kg) of saline (n = 10), HES 70/0.5--0.55 (molecular weight in kD/degree of substitution; n = 10), HES 130/0.38--0.45 (n = 10), HES 200/0.6--0.66 (n = 10), or HES 450/0.7--0.8 (n = 10) in otherwise healthy patients scheduled for elective surgery. Collagen and epinephrine were used as agonists for assessment of platelet function analyzer closure times. Flow cytom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
140
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(154 citation statements)
references
References 24 publications
9
140
1
4
Order By: Relevance
“…The lower MW TS has an average MW of 130 kD and a range from 110 to 150 kD,25 and has a clearance that is 26‐ to 31‐fold faster than HS,17 with a terminal half‐life after a single bolus of about 12 hours. The persistence of the prolonged CT for up to 24 hours might also have been seen because the larger HES molecules are more likely to impair platelet function 20. This property might have also resulted in the relatively slower rate of aggregation of platelets seen in the HS group with optical aggregometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower MW TS has an average MW of 130 kD and a range from 110 to 150 kD,25 and has a clearance that is 26‐ to 31‐fold faster than HS,17 with a terminal half‐life after a single bolus of about 12 hours. The persistence of the prolonged CT for up to 24 hours might also have been seen because the larger HES molecules are more likely to impair platelet function 20. This property might have also resulted in the relatively slower rate of aggregation of platelets seen in the HS group with optical aggregometry.…”
Section: Discussionmentioning
confidence: 99%
“…While this property decreases the risk for tissue accumulation, it also shortens the duration of effect 17. Formulations with increased molecular weight and higher molar substitution ratios are more likely to interfere with coagulation 4, 18, 19, 20…”
mentioning
confidence: 99%
“…In the present study, neither modern HES nor gelatin altered platelet MCF, even after CPB, which is a very important property of colloid solution administered after cardiac surgery. The minimal effect of HES 130/0.38-0.45 on platelets has also been demonstrated (Franz et al 2001). …”
Section: Mechanisms Of Colloid-induced Coagulopathymentioning
confidence: 91%
“…53,54,64 Several mechanisms have been proposed: some studies have shown that colloids may reduce levels of von Willebrand factor (vWF) and factor VIII, 65,66 whereas other studies have reported on masked expression of glycoprotein IIb/IIIa on activated platelets. 67,68 More recently, an acquired deficiency of fibrinogen with abnormal fibrin polymerization have been proposed as the main determinant of dilutional coagulopathy. 69,70 The dilutional coagulopathy observed after administration of moderate amounts of hydroxyethyl starch solutions could be completely corrected by administration of fibrinogen concentrate.…”
Section: Dilutionmentioning
confidence: 99%